Analysis of the electro-thermo-convection induced by a strong unipolar injection between two concentric or eccentric cylinders - Hassen, Walid; Öztop, Hakan Fehmi; Kolsi, Lioua; Borjini, Mohamed Naceur; Abu-Hamdeh, Nidal (Taylor & Francis Inc, 2017)
A computational study has been performed to see the effects of electro-thermo-convection induced via a strong unipolar injection between two concentric or eccentric cylinders using the finite volume method. The parameters are taken in the range of radius ratio 0.1?0.9, injection strength in the range of 1C20, mobility number changes in the range 4M150, electric Rayleigh number in the range of 100T800, and Rayleigh number changes in the range of 5000Ra25000. It is observed that the most important effective parameter is radius ratio, which affects both heat and fluid flow. Moreover, electrical Rayleigh numbers suppress the thermo-convection and in any case higher transfer is observed due to electric charge injection.
Keywords: Dielectric Liquid; Heat-Transfer; Natural-Convection; Layer; Nanofluid; Enclosure; Patterns; Geometry; Fluid; Field